ASSESSMENT OF THE TOURIST ATTRACTIVENESS OF GLOBAL GEOPARKS IN EUROPE - Lushchyk, M.; Mokryy, V.; Moscvyak, Ya.; Teodorovych , L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article provides an inventory of geoparks from the list of the UNESCO Global Geoparks Network. It is noted that geoparks as important tourist attractions have been the subject of scientific attention of many authors, but the data presented in these publications are outdated and can not claim to be relevant to the current state of the geoparks network, as it is quite dynamic and changes every year. The research of the chosen topic in the scientific domestic and foreign literature is characterized. The insufficiency of the tourism research of the UNESCO geoparks system is pointed out. The structural-territorial analysis of the distribution of objects is performed: absolute and relative indicators of the number of objects by macroregions are established. A cartographic model of the distribution of objects on the planet is presented. Monitoring of a specific set of geotourism attractions within each of the geoparks is done taking into account the following thematic types: geological and geomorphological (geological and geomorphological formations - the mountains, intermountain basins and gorges, craters and cones of volcanoes, river valleys, deltas and canyons, lakes, waterfalls, sea coasts, deserts and aeolian, glaciers and glacial, karst and pseudo-karst landforms, geological forms and phenomena - the minerals, rocks, structural and tectonic formations, paleontological fossils, geothermal phenomena; geological and geomorphological processes - volcanic eruptions, geyser explosions, avalanches, coastal processes on sea and lake coasts, melting glaciers, dune movements, erosion processes); industrial (the open and underground mine workings, clay and sand quarries, pits, exploratory shafts, drain lines, rock dumps, tunnels, catacombs, surface and underground military objects, engineering and geological activities, construction of tunnels, construction of roads and highways, use of geothermal water); cultural and cognitive (works of material culture are different buildings made of natural materials and the elements of their arrangement, stone pyramids, rock cities and temples, the stone artefacts, the stone elements of urban infrastructure, the works of art, jewellery, museum and other expositions, open-air expositions, such places of fossils, supporting stratigraphic sections, places of minerals and rocks location); tourist and infrastructural attractions (availability of the geopark for the access by several types of transport, several tourist accommodation options, currency exchange offices, recreation facilities, parking lots, places for tents; Tourist Information Centres; marked tourist routes for the needs of several types of tourism (cycling, green-, caving, water- tourism); marking of tourist attractions (information stands. Information support of tourism (creating internet portals of the geopark, mobile applications); accessibility of the geopark to the inclusive tourists). According to the indicators of occupancy of various thematic blocks, geoparks were ranked according to the scale of levels of attractiveness.
Keywords: geoparks; geomorphosites; geotourism attractions; geotourism attractiveness